Meta‐analysis of negative pressure wound therapy of closed groin incisions in arterial surgery. Issue 4 (6th February 2019) - Svensson‐Björk, R.; Zarrouk, M.; Asciutto, G.; Hasselmann, J.; Acosta, S.
Abstract : Background: Surgical‐site infection (SSI) after groin incisions for arterial surgery is common and may lead to amputation or death. Incisional negative pressure wound therapy (NPWT) dressings have been suggested to reduce SSIs. The aim of this systematic review with meta‐analysis was to assess the effects of incisional NPWT on the incidence of SSI in closed groin incisions after arterial surgery. Methods: A study protocol for this systematic review of RCTs was published in Prospero (CRD42018090298) a priori, with predefined search, inclusion and exclusion criteria. The records generated by the systematic research were screened for relevance by title and abstract and in full text by two of the authors independently. The selected articles were rated for bias according to the Cochrane risk‐of‐bias tool. Results: Among 1567 records generated by the search, seven RCTs were identified, including 1049 incisions. Meta‐analysis showed a reduction in SSI with incisional NPWT (odds ratio (OR) 0·35, 95 per cent c.i. 0·24 to 0·50; P  < 0·001). The heterogeneity between the included studies was low ( I 2  = 0 per cent). The quality of evidence was graded as moderate. Two studies had multiple domains in the Cochrane risk‐of‐bias tool rated as high risk of bias. A subgroup meta‐analysis of three studies of lower limb revascularization procedures only (363 incisions) demonstrated a similar reduction in SSI (OR 0·37, 0·22 to 0·63; P  < 0·001; I 2  = 0 per cent). Conclusion: Incisional NPWT after groin incisions for arterial surgery reduced the incidence of SSI compared with standard wound dressings. The risk of bias highlighted the need for a high‐quality RCT with cost‐effectiveness analysis. Abstract : This systematic review with meta‐analysis of RCTs only evaluated the use of incisional negative pressure wound therapy versus standard dressings on sutured incisions after groin incisions in arterial surgery for the prevention of surgical‐site infections. Meta‐analysis of the seven included studies showed a significant reduction in surgical‐site infections with the incisional negative pressure therapy dressing. Needs cost‐effectiveness analysis